Social Networking as Support Tool for Online Teaching and Learning Factors and Contributions - Sulaiman, Hamzah Asyrani; Ramlee, Ridza Azri; Othman, Mohd Azlishah; Misran, Mohamad Harris (2013)
Creating a good and stylish online learning for education is always bringing a good response to student especially for long-distance learning. The outcome is clear; which is to expand the capability of online education for all people around the globe by giving them a chance to study wherever they live and work as long they have good Internet access. Immersive learning as we all know consisting of the virtual reality aspect that bring educator and learner closer without having them to leave their place in order to gain knowledge and further their study. This paper studied the requirement to perform immersive learning while characterizing each challenge that we must face to perform a good online learning. We also numbered few technologies that could benefits the online learning either through website or online video conferencing.